Arthritis Research Methods and Protocols - Shiozawa, Shunichi; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2014)
Arthritis Research: Methods and Protocols, Second Edition expands upon the first edition to present new and current techniques for the research of arthritis and related conditions. A compendium of leaders in the field contribute chapters that cover practical research methods such as the intravital multiphoton microscopy technique, techniques for evaluating exhausted CD8 T cell and for studying nucleic acid sensors and their effects, methods for in vivo tetracycline-controlled transgenic mice and T cell receptor transgenic mice, protocols to detect V(D)J recombination products and microRNA, and the technique to make bleomycin-induced dermal fibrosis. Written in the successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, Arthritis Research: Methods and Protocols, Second Edition will serve both professionals and novices with state-of-the-art techniques pertaining to this fascinating research field.
Intravital Multiphoton Microscopy for Dissecting Cellular Dynamics in Arthritic Inflammation and Bone Destruction -- Monitoring Multifunctionality of Immune-Exhausted CD8 T in Cancer Patients -- Characterization of Innate Immune Signalings Stimulated by Ligands for Pattern Recognition Receptors -- Principled for the Use of in vivo Transgene Techniques: Overview and an Introductory Practical Guide for the Selection of Tetracycline-Controlled Transgenic Mice -- Unraveling Autoimmunity with the Adoptive Transfer of T Cells from TCR-Transgenic Mice -- In Vivo Cell Transfer Assay to Detect Autoreactive T Cell Subsets -- Characterization of microRNAs and Their Targets -- Studies on the T Cell Receptor (TCR) Revision of Autoantibody-Inducing CD4T (aiCD4 T) Cell -- Basic Techniques for Studies of iNKT Cells and MAIT Cells -- Induction of de novo Autoimmune Disease in Normal Mice Upon Repeated Immunization with Antigen -- Mouse Models of Experimental Dermal Fibrosis: The Bleomycin-Induced Dermal Fibrosis -- Screening for Novel Serum Biomarker for Monitoring Disease Activity in Rheumatoid Arthritis Using iTRAQ Technology Based Quantitative Proteomic Approach -- Genome-Wide Genetic Study in Autoimmune Disease Prone Mice -- Bayesian Systems-Based Genetic Association Analysis with Effect Strength Estimation and Omic Wide Interpretation: A Case Study in Rheumatoid Arthritis -- Sample Processing, Protocol and Statistical Analysis of the Time of Flight Secondary Ion Mass Spectrometry (ToF-SIMS) of Protein, Cell and Tissue Samples -- Label-Free Imaging of Adipogenesis by Coherent Anti-Stokes Raman Scattering Microscopy.
Keywords: Molecular biology; Orthopedics; Rheumatology; Molecular Medicine; Orthopedics; Rheumatology